Development and evaluation of a personalised psychological intervention to improve adherence to photoprotection in adults with Xeroderma Pigmentosum (XP) - Robert Sarkany; Jessica Walburn; Rebecca Anderson; Vera Araujo-Soares; Janette Boadu; Martha Canfield; Lesley Foster; Paul McCrone; Myfanwy Morgan; Sam Norton; Kirby Sainsbury; John Weinman (NIHR Journals Library, 2024)
Background Poor adherence to photoprotection from ultraviolet radiation in the rare disease xeroderma pigmentosum can be life-threatening due to heightened risk of skin cancers. This novel, two-phase research programme used mixed methods to investigate photoprotection in xeroderma pigmentosum, and its psychosocial impact, to develop an intervention to improve photoprotection. Objective(s) Phase I: To identify barriers to optimal photoprotection. Phase II: To design and test a personalised psychological intervention to improve photoprotection. Design Phase I: Interview study; n-of-1 photoprotection study; objective measurement of ultraviolet radiation exposure study; international cross-sectional survey. Phase II: Consensus conference to synthesise findings and determine targets/priorities for intervention; intervention development using Intervention mapping; randomised controlled trial to test efficacy, cost-effectiveness and intervention mechanisms. Settings for Phases I and II National Xeroderma Pigmentosum Service, Guy's and St Thomas' NHS Foundation Trust, London, United Kingdom; Specialist xeroderma pigmentosum clinics in Regensburg, Germany, Japan, Tunisia; Patient support organisations in France and USA. Participants Children < 16 (Phase I only) and adults (> 16) diagnosed with xeroderma pigmentosum. Intervention (Phase II) XPAND is a seven-session personalised psychological intervention designed to be facilitated by non-psychologists, delivered in spring to summer 2018 versus wait list control (intervention in spring to summer 2019). Main trial outcome measure (Phase II) Average daily ultraviolet radiation dose to the face calculated by combining objective ultraviolet radiation exposure with self-reported photoprotection. Results Phase I: Varying levels of photoprotection were found, with most participants doing less than clinically recommended. The international survey (N = 156) and estimation of ultraviolet radiation dose-to-face (N = 41) found that adults had worse photoprotection than the 'cared for' sample, but that overall the total dose-to-face was similar in the two groups because the 'cared for' group were outside more. The n-of-1 study (N = 20) showed that fluctuations in protection were associated with time of day, weekday versus weekend, environmental risk perceptions and symptoms resulting from exposure, self-regulatory and psychological constructs. The qualitative study (N = 25) identified three modes of adaptation to photoprotection: (1) 'dominated', (2)'integrated' and (3) 'resistant'. Modifiable drivers of photoprotection behaviour were identified in the survey studies, including belief-based predictors and the important role of habits. These combined findings informed the development and targets of the XPAND intervention. Phase II: The intervention group (n = 6) had significantly lower daily average ultraviolet radiation dose-to-face (primary outcome) compared to control (n = 7) (−0.25 Standard Erythemal Dose, p < 0.001, Hedge's g = 2.2). Health economic analysis indicated that the intervention was associated with lower costs than control (£2642, 95% confidence interval −£8715 to £3873) and fewer quality-adjusted life-years (−0.0141, 95% confidence interval −0.0369 to 0.0028). Interviews found that XPAND was acceptable, and that greater automaticity and confidence contributed to improvements in photoprotection. Limitations: Due to the low prevalence of xeroderma pigmentosum, piloting was not possible and participant numbers in the trial were small, and some analyses were underpowered. The randomisation resulted in an imbalance in between-group baseline measures of ultraviolet radiation protection, and there was a lack of participant blinding. The magnitude, duration, cost-effectiveness and generalisability of the intervention are difficult to evaluate. The small sample size means we have to be cautious about both costs and QALYs, and in the short term we probably would not expect QALY differences given the long-term aims of photoprotection. Conclusions Phases I and II: Determinants of inadequate photoprotection in xeroderma pigmentosum were identified and successfully targeted in a comprehensive and personalised intervention, which was acceptable to patients. The reduction in daily ultraviolet radiation dose to the face was larger than the clinically agreed difference anticipated to be effective in reducing the number of skin cancers in xeroderma pigmentosum. XPAND was associated with lower costs, below the incremental cost-effectiveness threshold of £20,000 on a cost-effectiveness plane, due to less service use, and quality-adjusted life-years were similar, although cost-effectiveness results did not reach statistical significance. Rare disease research is challenging; the success of XPAND shows that scientific rigour is possible and intervention efforts worthwhile. Future work:There is scope for extending the intervention in xeroderma pigmentosum and other at-risk groups. There is a need to ascertain whether the XPAND intervention can be effective for parents/carers who play the key role in ensuring photoprotection in their children or cognitively impaired adult relatives. It will be important to evaluate (1) the duration of the positive effects of XPAND intervention and the potential for booster sessions to maintain the changes in ultraviolet radiation protection, (2) whether specialist nurses can deliver XPAND in routine clinical settings, (3) to test n-of-1 'micro' trial designs to evaluate efficacy in individual patients and (4) to adapt the intervention for a web-based digital delivery which could be accessed by an international xeroderma pigmentosum population. Future work should adapt and evaluate the XPAND intervention (1) for use with other groups of adults at higher risk of non-malignant skin cancers and (2) to investigate and evaluate novel intervention methods to tackle 'when' and for 'how long' patients are outdoors, together with habit-based interventions for sunscreen application which could be appropriate to prevent ultraviolet radiation damage in the healthy population. Trial registration This trial is registered as ClinicalTrials.gov NCT03445052. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research (NIHR award ref: RP-PG-1212-20009) programme and is published in full in Programme Grants for Applied Research; Vol. 12, No. 3. See the NIHR Funding and Awards website for further award information. Plain language summary People with xeroderma pigmentosum have a genetic condition that stops their skin repairing damage from ultraviolet radiation, and means they are more likely to develop skin cancers. The only way to reduce this risk is to protect by staying indoors and using items like hats, glasses and sunscreen when outside. People with xeroderma pigmentosum can find it difficult to protect all the time. We investigated what makes it harder or easier to protect and tested whether an intervention focusing on these things was successful at improving photoprotection. We found that what made protection difficult included doubting the need to protect in different situations (e.g. cloudy weather), concerns about protecting (e.g. looking different) and not having photoprotection routines. We designed XPAND with our patient and public involvement panel, clinicians and researchers. It involved seven tailored conversations (virtual or live) between a patient and a healthcare professional to identify what motivates them to protect and what makes it harder; we used our studies to create materials (e.g. a magazine describing ways to overcome barriers). We measured the amount of ultraviolet radiation reaching the face ('dose-to-face') before and after XPAND, compared to a group who did not do the sessions. Our way of measuring was new, using an ultraviolet radiation monitor worn on the wrist and photoprotection recorded in a diary. The XPAND group had lower dose-to-face afterwards than those who did not receive XPAND immediately, suggesting that it could be successful. However, because we were comparing small groups, we cannot be certain that the result was because of XPAND or the group already had a lower dose-to-face.